Spatial and temporal heterogeneity of the density of Borrelia burgdorferi‐infected Ixodes ricinus ticks across a landscape: A 5‐year study in southern England. Issue 3 (6th May 2022) - Medlock, Jolyon M.; Vaux, Alexander G. C.; Gandy, Sara; Cull, Benjamin; McGinley, Liz; Gillingham, Emma; Catton, Matthew; Pullan, Steven T.; Hansford, Kayleigh M.
Abstract: The density of Borrelia burgdorferi ‐infected Ixodes ricinus nymphs (DIN) was investigated during 2013–2017 across a Lyme disease‐endemic landscape in southern England. The density of nymphs (DON), nymph infection prevalence (NIP), and DIN varied across five different natural habitats, with the highest DIN in woodland edge and high biodiversity woodlands. DIN was significantly lower in scrub grassland compared to the woodland edge, with low DON and no evidence of infection in ticks in non‐scrub grassland. Over the 5 years, DON, NIP and DIN were comparable within habitats, except in 2014, with NIP varying three‐fold and DIN significantly lower compared to 2015–2017. Borrelia garinii was most common, with bird‐associated Borrelia ( B . garinii/valaisiana ) accounting for 70% of all typed sequences. Borrelia burgdorferi sensu stricto was more common than B . afzelii . Borrelia afzelii was more common in scrub grassland than woodland and absent in some years. The possible impact of scrub on grazed grassland, management of ecotonal woodland margins with public access, and the possible role of birds/gamebirds impacting NIP are discussed. Mean NIP was 7.6%, highlighting the potential risk posed by B . burgdorferi in this endemic area. There is a need for continued research to understand its complex ecology and identify strategies for minimizing risk to public health, through habitat/game management and public awareness. Abstract : Ixodes ricinus nymph density and Borrelia ‐infected tick nymph prevalence (7.6%) varied widely across a rural landscape both spatially between habitats and temporally over the 5‐year study (2013–2017). Highest tick densities and Borrelia prevalences were in woodland and woodland edge habitats, varying three‐fold between years. Ticks and Borrelia were largely absent from calcareous grassland. Borrelia garinii/valaisiana accounted for 70% of typed sequences. Borrelia burgdorferi sensu stricto was more common than B . afzelii . Borrelia afzelii was more common in grazed grassland but absent in some years.